2018
DOI: 10.1088/2399-6528/aaab0d
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Stokes laws for active colloids and their applications

Abstract: The force per unit area on the surface of a colloidal particle is a fundamental dynamical quantity in the mechanics and statistical mechanics of colloidal suspensions. Here we compute it in the limit of slow viscous flow for a suspension of N spherical active colloids in which activity is represented by surface slip. Our result is best expressed as a set of linear relations, the 'generalized Stokes laws', between the coefficients of a tensorial spherical harmonic expansion of the force per unit area and the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 123 publications
(267 reference statements)
1
58
0
Order By: Relevance
“…We emphasize that this expression is not limited to the translationally invariant Green's function of unbounded flow, 8πη G(r) = (∇ 2 I − ∇∇)r, but holds generally for any Green's function and is both symmetric and positivedefinite [19,20]. The mutual friction tensors decay inversely with distance in an unbounded fluid and more rapidly in the proximity of boundaries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasize that this expression is not limited to the translationally invariant Green's function of unbounded flow, 8πη G(r) = (∇ 2 I − ∇∇)r, but holds generally for any Green's function and is both symmetric and positivedefinite [19,20]. The mutual friction tensors decay inversely with distance in an unbounded fluid and more rapidly in the proximity of boundaries.…”
mentioning
confidence: 99%
“…The bold-face notation, with Cartesian indices suppressed, is used for both vectors and tensors. In the limit of slow viscous flow in the fluid, the friction tensors can be calculated from the Stokes equation using a variety of methods [16][17][18][19][20]. To leading order the result is…”
mentioning
confidence: 99%
“…n ls n la n lt -of rank l,l 1 andl 2; they correspond to symmetric traceless, antisymmetric and trace combinations of the reducible indices. We denote the three irreducible parts by s ( ) V l and the suffixes s = s a t , , are self-explanatory [30,31]. For convenience, we introduce special notations for the s = l a 1 and s = l a 2 coefficients.…”
Section: Brownian Microhydrodynamics Of Active and Passive Spheresmentioning
confidence: 99%
“…By invoking the linearity of the Stokes equations, it can be shown that the contact forces and torques are linear functions of the boundary condition [31]. They are related to linear velocity V m , angular velocity W m and irreducible modes of active slip s ( ) V m l as, In the equation above, we have used the summation convention for repeated particle (n, m) and mode s ( ) l indices.…”
Section: Brownian Microhydrodynamics Of Active and Passive Spheresmentioning
confidence: 99%
See 1 more Smart Citation